Cascade anchoring strategy for general mass production of high-loading single-atomic metal-nitrogen catalysts - Zhao, Lu; Zhang, Yun; Huang, Lin-Bo; Liu, Xiao-Zhi; Zhang, Qing-Hua; He, Chao; Wu, Ze-Yuan; Zhang, Lin-Juan; Wu, Jinpeng; Yang, Wanli; Gu, Lin; Hu, Jin-Song; et al. (Nature communications, 2019)
Although single-atomically dispersed metal-N x on carbon support (M-NC) has great potential in heterogeneous catalysis, the scalable synthesis of such single-atom catalysts (SACs) with high-loading metal-N x is greatly challenging since the loading and single-atomic dispersion have to be balanced at high temperature for forming metal-N x . Herein, we develop a general cascade anchoring strategy for the mass production of a series of M-NC SACs with a metal loading up to 12.1 wt%. Systematic investigation reveals that the chelation of metal ions, physical isolation of chelate complex upon high loading, and the binding with N-species at elevated temperature are essential to achieving high-loading M-NC SACs. As a demonstration, high-loading Fe-NC SAC shows superior electrocatalytic performance for O 2 reduction and Ni-NC SAC exhibits high electrocatalytic activity for CO 2 reduction. The strategy paves a universal way to produce stable M-NC SAC with high-density metal-N x sites for diverse high-performance applications. Although single atom catalysts (SACs) with high-loading metal-Nx have great potential in heterogeneous catalysis, their scalable synthesis remains challenging. Here, the authors develop a general cascade anchoring strategy for the mass production of a series of metal-Nx SACs with a metal loading up to 12.1 wt%.